Artificial Intelligence-Enhanced Learning in Science Education to Improve Scientific Literacy, Critical Thinking, and Personalized Learning Outcomes - Utami, Ayu Rischi (Scientica Education Journal, 2025)
This study aims to examine the effectiveness of artificial intelligence (AI)-enhanced learning in improving students’ scientific literacy, critical thinking skills, and personalized learning outcomes in science education. The research employed a quantitative approach using a quasi-experimental design with a non-equivalent control group. The participants consisted of two groups: an experimental group taught using AI-enhanced learning supported by intelligent tutoring systems and adaptive feedback, and a control group taught using conventional methods. Data were collected through a scientific literacy test, a critical thinking skills test, and a personalized learning questionnaire. The results showed that the experimental group achieved significantly higher post-test scores compared to the control group. The normalized gain (N-gain) analysis indicated that the experimental group reached a medium to high level of improvement, while the control group remained in the low to medium category. Statistical testing using an independent sample t-test revealed a significant difference between the two groups (p < 0.05). Furthermore, AI-enhanced learning significantly improved students’ ability to interpret data, evaluate evidence, think critically, and engage in personalized learning processes. These findings suggest that AI-based learning is an effective and innovative instructional strategy for enhancing both cognitive and adaptive learning outcomes in science education.